A modular femoral stem and method of making a zoned gradient coating thereon
Patent Information
- Application Number
- CN202611410341.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-11
- Publication Date
- 2026-10-20
AI Technical Summary
[0011]本发明的目的在于提供一种组合式股骨柄的柄体,以解决现有柄体表面涂层设计单一、缺乏区域差异化处理、涂层与抛光区域界面过渡不佳等技术问题,同时提高其表面耐磨性、生物活性与骨整合能力,避免术后大腿痛
[0032]1. 分区梯度涂层设计,满足不同区域的差异化需求:近端区域采用纯钛+HA双涂层(300μm Ti + 50μm HA),提供高结合强度和骨传导性,保证初期稳定性;中远端采用较厚HA涂层(150μm),实现充分的骨长入;远端镜面抛光(Ra≤0.8μm)允许微动,避免大腿痛。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0003] This invention belongs to the field of orthopedic implant technology, specifically relating to a combined femoral stem for total hip arthroplasty, its surface coating structure, and preparation method. Background Technology
[0005] Total hip arthroplasty is an effective treatment for end-stage hip joint disease. The modular femoral stem, a core component of the artificial hip joint, consists of a detachably connected femoral neck and stem. The stem is permanently implanted within the femoral medullary cavity, and its design must balance biological fixation, mechanical transmission, and long-term stability.
[0006] Currently, the femoral stems widely used in clinical practice are mostly made of titanium alloy, with a surface coating to promote osseointegration. In existing technologies, the stem surface coating typically uses a single-structure hydroxyapatite (HA) coating or a titanium coating, with the coating distribution often being full or partial coverage. However, the mechanical environment and biological requirements experienced by different regions of the stem within the medullary canal vary significantly: the proximal region bears the main compressive stress and requires strong bone ingrowth and initial stability; the mid-to-distal region requires good osseointegration to transfer loads; and if the distal region has an excessively thick coating or a rough surface, it may cause postoperative thigh pain due to rigid contact with the endosteal membrane.
[0007] Existing research has shown that a zoned surface treatment approach can optimize the mechanical conduction and osseointegration of the handle. However, current technologies lack systematic optimization schemes for coating types, thicknesses, and transition methods in different areas. Furthermore, the interface transition between the coated and polished areas is often a weak point where stress concentration occurs, easily leading to coating peeling or interface failure.
[0008] Ti-6Al-7Nb (TC20) titanium alloy is a novel titanium alloy for surgical implants. It completely replaces the vanadium (V) element in TC4 alloy with bio-inert and non-toxic niobium (Nb), exhibiting comparable strength, toughness, and fatigue properties to TC4, while demonstrating superior resistance to bodily fluid corrosion and biocompatibility. However, there are currently no reports on combined femoral stem products that integrate TC20 titanium alloy with zoned gradient coating technology.
[0009] Therefore, there is an urgent need to develop a combined femoral stem body technology solution that can design differentiated coatings according to the biological and mechanical needs of different regions and achieve a performance gradient transition between different regions. Summary of the Invention
[0011] The purpose of this invention is to provide a composite femoral stem to solve the technical problems of existing stem surface coating designs that are monotonous, lack regional differentiation treatment, and poor transition between the coating and polished areas. At the same time, it improves the surface wear resistance, bioactivity and bone integration ability, and avoids postoperative thigh pain.
[0012] Another object of the present invention is to provide a method for preparing the combined femoral stem.
[0013] Technical solution
[0014] To achieve the above objectives, the present invention adopts the following technical solution.
[0015] A composite femoral stem for use in a hip joint prosthesis includes a stem body made of titanium alloy, wherein the stem body is divided into a proximal region, a mid-section transition region, a mid-distal region and a distal region along its longitudinal axis.
[0016] The proximal region surface is coated with a first composite coating, which comprises a pure titanium coating and a hydroxyapatite coating. The pure titanium coating has a thickness of 300±50 μm, and the hydroxyapatite coating has a thickness of 50±10 μm. The proximal region adopts a double-coating structure of pure titanium + HA. The pure titanium bottom layer provides high-strength bonding with the matrix, while the HA surface layer provides excellent osteoconductivity, promoting bone ingrowth and initial fixation.
[0017] A second coating is provided on the surface of the intermediate transition region. This second coating is a mixed transition coating of pure titanium and hydroxyapatite, with a thickness of 50-150 μm. The hydroxyapatite content gradually increases from the proximal end to the distal end, with a proximal hydroxyapatite content of 30±5% and a distal hydroxyapatite content of 70±5%. This gradient design effectively eliminates the interface of abrupt performance changes between the proximal HA coating and the mid-to-distal HA coating, avoiding the risk of coating stress concentration and peeling.
[0018] A third coating, which is a hydroxyapatite coating, with a thickness of 150±20 μm, is applied to the surface of the mid-distal region. The mid-distal region employs a thicker pure HA coating to provide ample space for bone ingrowth, achieving robust biological fixation between the prosthesis and the femoral shaft.
[0019] The distal region has a mirror-polished surface with a surface roughness Ra≤0.8 μm. The distal mirror-polished design allows for micro-movement of the stem within the medullary cavity, avoiding stress shielding and thigh pain caused by distal rigid locking.
[0020] Preferably, the length of the proximal region is 20-36 mm, the length of the mid-section transition region is a transition joint, the length of the hydroxyapatite coating in the mid-to-distal region is 70-134 mm, and the length of the distal mirror-polished region is 10 mm.
[0021] Preferably, the material of the handle base is TC20 titanium alloy (Ti-6Al-7Nb), whose chemical composition, by mass fraction, contains: Al 5.5-6.5%, Nb 6.5-7.5%, Fe≤0.25%, O≤0.20%, C≤0.08%, N≤0.05%, H≤0.009%, with the balance being Ti and unavoidable impurities. The TC20 alloy replaces vanadium in the TC4 alloy with non-toxic niobium, eliminating the potential biotoxicity of vanadium and exhibiting better biocompatibility and corrosion resistance.
[0022] Preferably, the total length of the handle is 100-180 mm, with 16 specifications provided in increments of 5 mm.
[0023] Preferably, the pure titanium coating and hydroxyapatite coating in the near-end region and the hydroxyapatite coating in the mid-far-end region are prepared by atmospheric plasma spraying; the transition coating in the mid-section transition region is prepared by co-spraying, wherein the powder feeding rate of hydroxyapatite powder increases linearly with the spraying time during the spraying process, and the powder feeding rate of pure titanium powder decreases linearly with the spraying time.
[0024] This invention also provides a method for preparing the above-mentioned combined femoral stem, comprising the following steps:
[0025] (1) TC20 titanium alloy (Ti-6Al-7Nb) is selected as the material and forged and machined into a handle blank. The blank has a proximal region, a middle transition region, a mid-far end region and a distal region arranged sequentially along the longitudinal axis. (2) The blank is heat-treated to obtain an annealed structure. (3) The proximal region, middle transition region and mid-far end region of the handle body are pre-treated, including cleaning, sandblasting roughening and activation. The distal region is mirror polished to make the surface roughness Ra≤0.8 μm. (4) Atmospheric plasma spraying process is used to sequentially spray a pure titanium coating and a hydroxyapatite coating on the surface of the proximal region. The thickness of the pure titanium coating is controlled to be 300±50 μm and the thickness of the hydroxyapatite coating is controlled to be 50±10 μm. μm; (5) Using a co-spraying process, a mixed transition coating of pure titanium and hydroxyapatite is sprayed on the surface of the middle transition area. During the spraying process, the powder feeding rate of hydroxyapatite powder increases linearly with the spraying time, and the powder feeding rate of pure titanium powder decreases linearly with the spraying time; (6) Using an atmospheric plasma spraying process, a hydroxyapatite coating is sprayed on the surface of the middle and far end areas, and the thickness is controlled to be 150±20 μm; (7) The coating is post-treated, including sealing treatment and low temperature heat treatment.
[0026] Preferably, the heat treatment in step (2) is vacuum annealing, with an annealing temperature of 700-800℃ and a holding time of 1-2 hours.
[0027] Preferably, the sandblasting roughening in step (3) results in a surface roughness Ra of 3-5 μm.
[0028] Preferably, the atmospheric plasma spraying process parameters in steps (4), (5) and (6) are: spraying current 500-700 A, spraying voltage 40-60 V, main gas flow rate 30-50 L / min, and powder feeding rate 20-40 g / min.
[0029] Preferably, the post-processing in step (7) includes: sealing the pores with a biocompatible sealant, and low-temperature heat treatment at 500-650°C.
[0030] Beneficial effects
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] 1. The zoned gradient coating design meets the differentiated needs of different regions: the proximal region adopts a pure titanium + HA dual coating (300μm Ti + 50μm HA) to provide high bonding strength and osteoconductivity, ensuring initial stability; the mid-distal region adopts a thicker HA coating (150μm) to achieve sufficient bone ingrowth; the distal region is mirror polished (Ra≤0.8μm) to allow micro-movement and avoid thigh pain.
[0033] 2. The intermediate transition region achieves a gradient transition of material composition and eliminates the interface of sudden performance changes: the HA content in the transition coating increases gradually from the proximal end to the distal end (30%→70%), so that the mechanical and biological properties between the proximal double coating region and the mid-to-distal HA coating region are smoothly transitioned, effectively avoiding the risk of coating stress concentration and interface peeling.
[0034] 3. The use of vanadium-free TC20 titanium alloy (Ti-6Al-7Nb) matrix provides higher biosafety: vanadium in TC4 alloy is replaced with bioinert and non-toxic niobium, completely eliminating the potential biotoxicity risk of vanadium.
[0035] 4. Multi-specification series design to meet different anatomical needs: 16 specifications, with a total handle length of 100-180mm increasing in 5mm increments, covering the medullary cavity anatomy characteristics of patients with different body types. Doctors can choose the most suitable specification according to the patient's specific situation.
[0036] 5. Optimized coating thickness design, balancing bone ingrowth and mechanical properties: The thickness design of 300μm pure titanium layer at the proximal end + 50μm HA layer and 150μm HA layer at the mid-distal end provides an ideal three-dimensional structure for bone tissue ingrowth, while ensuring the bonding strength between the coating and the substrate.
[0037] 6. Extend the lifespan of the prosthesis: The synergistic design of zoned coating, gradient transition and mirror polishing improves the long-term stability and bio-fixation effect of the stem, which helps to extend the revision cycle. Attached Figure Description
[0039] Figure 1 This is a schematic cross-sectional view of the overall structure of the combined femoral stem body of the present invention;
[0041] Figure 2 for Figure 1 A partially enlarged cross-sectional view of the composite coating at point A in the mid-to-near region;
[0043] Figure 3 for Figure 1 A magnified cross-sectional view of the gradient coating at point B in the mid-section transition region;
[0045] In the figure: 1-stem body substrate, 2-proximal region, 3-mid-section transition region, 4-mid-distal region, 5-distal region, 6-pure titanium coating, 7-hydroxyapatite (HA) coating, 8-transition coating. Detailed Implementation
[0047] The specific embodiments of the present invention will now be described in detail with reference to the accompanying drawings.
[0048] like Figure 1 As shown, the main body of the combined femoral stem provided by the present invention is a stem base 1 formed by processing TC20 titanium alloy (Ti-6Al-7Nb). The stem base 1 is divided into a proximal region 2, a mid-section transition region 3, a mid-distal region 4, and a distal region 5 along its longitudinal axis.
[0049] The chemical composition of TC20 titanium alloy is strictly controlled within the standard range: Al 5.5~6.5%, Nb 6.5~7.5%, Fe≤0.25%, O≤0.20%, C≤0.08%, N≤0.05%, H≤0.009%, with the balance being Ti. After vacuum annealing (700-800℃, holding for 1-2 hours), the mechanical properties meet the requirements of tensile strength ≥900 MPa, yield strength ≥800 MPa, and elongation ≥10%.
[0050] There are 16 different handle sizes, with the total handle length ranging from 100mm to 180mm, increasing in 5mm increments.
[0051] like Figure 2 As shown, a composite coating is prepared on the surface of the proximal region 2. This coating consists of two layers: a pure titanium coating 6 closely adhering to the substrate, with a thickness of 300±50 μm; and an outer hydroxyapatite (HA) coating 7, with a thickness of 50±10 μm. The pure titanium coating serves as a transition layer, improving the bonding strength between the substrate and the HA coating; the HA coating provides osteoconductivity, promoting osteoblast attachment and bone ingrowth.
[0052] like Figure 3 As shown, a transition coating 8 is prepared on the surface of the mid-section transition region 3. This coating is a mixture of pure titanium and HA, with the HA content increasing in a gradient from the proximal end to the distal end, where the HA content is 30±5% at the proximal end and 70±5% at the distal end. This gradient design eliminates the abrupt performance change between the proximal region and the mid-distal region.
[0053] An HA coating with a thickness of 150±20 μm was prepared on the surface of the mid-distal region 4 to provide sufficient space for bone ingrowth.
[0054] The distal region 5 has a mirror-polished surface with a surface roughness Ra≤0.8 μm, which allows the stem to move slightly within the medullary cavity and avoids rigid locking at the distal end.
[0055] In the specific preparation process, TC20 titanium alloy bars conforming to the standard are first forged and precision machined into a shank shape, and then vacuum annealed (700-800℃, held for 1-2 hours). Then, the proximal region, the middle transition region, and the mid-to-far region are sandblasted to achieve a surface roughness Ra of 3-5 μm, thereby increasing the coating adhesion area; the far region is mirror polished to achieve Ra ≤ 0.8 μm.
[0056] After cleaning and drying, an atmospheric plasma spraying process is used (spraying current 500-700A, spraying voltage 40-60V, main gas flow rate 30-50L / min, powder feeding rate 20-40g / min). First, a pure titanium coating (300±50 μm) is sprayed in the near-end region, followed by an HA coating (50±10 μm). Then, a co-spraying process is used to spray a mixed coating of pure titanium and HA in the middle transition region, with the HA powder feeding rate increasing linearly and the pure titanium powder feeding rate decreasing linearly. Finally, an HA coating (150±20 μm) is sprayed in the mid-to-far-end region.
[0057] After spraying, the coating is sealed and subjected to low-temperature heat treatment at 550-600℃ to eliminate internal stress in the coating and improve the crystallinity of HA and the bonding strength of the coating.
[0058] After implantation, the proximal double-coated area provides robust initial fixation and bone ingrowth, the mid-section gradient coating ensures a smooth performance transition, the mid-distal HA coating provides ample osseointegration, and the distal mirror-polished surface allows for micromovement to prevent thigh pain. The entire system combines high biocompatibility, excellent mechanical properties, and the ability to promote osseointegration.
[0059] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Any substitutions or improvements made under the premise of the present invention should be included within the protection scope of the present invention.
Claims
1. A composite femoral stem for use in hip joint prostheses, characterized in that, The device includes a stem base formed from titanium alloy, which is divided into a proximal region, a mid-section transition region, a mid-distal region, and a distal region along its longitudinal axis. The proximal region has a first composite coating, comprising a pure titanium coating and a hydroxyapatite coating. The pure titanium coating has a thickness of 300±50 μm, and the hydroxyapatite coating has a thickness of 50±10 μm. The mid-section transition region has a second coating, a mixed transition coating of pure titanium and hydroxyapatite, with a thickness of 50-150 μm, wherein the hydroxyapatite content gradually increases from the proximal end to the distal end. The mid-distal region has a third coating, also a hydroxyapatite coating, with a thickness of 150±20 μm. The distal region has a mirror-polished surface with a surface roughness Ra≤0.8 μm.
2. The stem of the combined femoral stem according to claim 1, characterized in that: In the transition coating of the middle transition region, the content of proximal hydroxyapatite is 30±5%, and the content of distal hydroxyapatite is 70±5%.
3. The stem of the combined femoral stem according to claim 1, characterized in that: The length of the proximal region is 20-36 mm, the length of the hydroxyapatite coating in the mid-distal region is 70-134 mm, and the length of the distal mirror-polished region is 10 mm.
4. The stem of the combined femoral stem according to claim 1, characterized in that: The material of the handle body base is Ti-6Al-7Nb titanium alloy, and its chemical composition, by mass fraction, contains: Al 5.5-6.5%, Nb 6.5-7.5%, Fe≤0.25%, O≤0.20%, C≤0.08%, N≤0.05%, H≤0.009%, with the balance being Ti and unavoidable impurities.
5. The stem of the combined femoral stem according to claim 1, characterized in that: The handle body has a total length of 100-180 mm, with 16 specifications in increments of 5 mm.
6. The stem of the combined femoral stem according to claim 1, characterized in that: The pure titanium coating and hydroxyapatite coating in the near-end region and the hydroxyapatite coating in the mid-far-end region are prepared by atmospheric plasma spraying; the transition coating in the mid-section transition region is prepared by co-spraying.
7. A method for preparing the stem of the combined femoral stem as described in any one of claims 1-6, characterized in that... Includes the following steps: (1) Select Ti-6Al-7Nb titanium alloy processing material, and forge and machine it into a shank blank. The blank has a proximal region, a middle transition region, a middle and distal region and a distal region arranged sequentially along the longitudinal axis. (2) Heat treat the blank to obtain an annealed structure; (3) Perform surface pretreatment on the proximal region, middle transition region and mid-to-far region of the handle body base, and perform mirror polishing on the far region. (4) Using atmospheric plasma spraying process, a pure titanium coating and a hydroxyapatite coating are sequentially sprayed on the surface of the near end region. The thickness of the pure titanium coating is controlled to be 300±50 μm and the thickness of the hydroxyapatite coating is controlled to be 50±10 μm. (5) A co-spraying process is adopted to spray a mixed transition coating of pure titanium and hydroxyapatite on the surface of the intermediate transition area. During the spraying process, the powder feeding rate of hydroxyapatite powder increases linearly with the spraying time. (6) An atmospheric plasma spraying process is used to spray a hydroxyapatite coating on the surface of the mid-to-far end region, with the thickness controlled to be 150±20 μm. (7) Post-treatment of the coating.
8. The method according to claim 7, characterized in that: The heat treatment in step (2) is vacuum annealing, with an annealing temperature of 700-800℃ and a holding time of 1-2 hours.
9. The method according to claim 7, characterized in that: The surface pretreatment in step (3) includes cleaning, sandblasting roughening and activation. Sandblasting roughening makes the surface roughness Ra reach 3-5 μm; the mirror polishing treatment makes the surface roughness Ra of the far region ≤ 0.8 μm.
10. The method according to claim 7, characterized in that: The post-processing in step (7) includes sealing and low-temperature heat treatment at 500-650°C.